2018
DOI: 10.1016/j.psychsport.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between cognitions, pacing strategies and performance in 16.1 km cycling time trials using a think aloud protocol

Abstract: Objectives Three studies involved the investigation of concurrent cognitive processes and pacing behaviour during a 16.1km cycling time trial (TT) using a novel Think Aloud (TA) protocol. Study 1 examined trained cyclist's cognitions over time whilst performing a real-life 16.1km time trial (TT), using TA protocol. Study 2, included both trained and untrained participants who performed a 16.1 km TT in a laboratory whilst using TA. Study 3 investigated participants' experiences of using TA during a TT performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 69 publications
4
64
0
1
Order By: Relevance
“…Thelwell et al (2018) stated that they adopted "the post-positivist approach to the data collection" (p. 136) in the qualitative phase, "but progressed via the adoption of a pragmatic stance to address the research question at a different level that in this case, required a shift from epistemological purity" (p. 139). Whitehead et al (2018) adopted an expansion approach, where a series of three studies were conducted to gain different insights into the same topic. They described assuming a post-positivist stance in the first two studies and switching to a relativist-interpretivist perspective in the third study.…”
Section: Paradigmatic Positioning Of Mmrmentioning
confidence: 99%
See 2 more Smart Citations
“…Thelwell et al (2018) stated that they adopted "the post-positivist approach to the data collection" (p. 136) in the qualitative phase, "but progressed via the adoption of a pragmatic stance to address the research question at a different level that in this case, required a shift from epistemological purity" (p. 139). Whitehead et al (2018) adopted an expansion approach, where a series of three studies were conducted to gain different insights into the same topic. They described assuming a post-positivist stance in the first two studies and switching to a relativist-interpretivist perspective in the third study.…”
Section: Paradigmatic Positioning Of Mmrmentioning
confidence: 99%
“…In terms of evaluating research rigour, some researchers addressed integrative quality criteria that they framed as applicable to the study as a whole (e.g., Karageorghis et al, 2018;Mallinson-Howard et al, 2018;Rumbold et al, 2018;Thrower et al, 2019), but more often quantitative and qualitative parts of the study were evaluated separately (e.g., Kacperski & Hall, 2017;Middleton et al, 2017;Redwood-Brown et al, 2018;Richard et al, 2017;Whitehead et al, 2018). From the integrative perspective, Thrower et al (2019) suggested that "taken as a whole, this study can be judged on the capacity to which it is relevant for the research questions, is transparent, has a rationale for using mixed methods, and requires the integration of mixed-method findings", while at the same time maintaining that "the quality criteria for each aspect of the study should be considered separately" (p. 4).…”
Section: Considerations Of Research Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…measuring self-efficacy during endurance performance poses practical difficulties, recent research suggests that a think-aloud protocol can be used with runners (Samson et al, 2017) and cyclists (Whitehead et al, 2017) to gain understanding of their thoughts. This may also provide further insight into the cyclical nature of self-regulation.…”
Section: Self-regulation In Endurance Sports 23mentioning
confidence: 99%
“…In this case, the reflections in the class journal were maintained and did not diminish neither were they abandoned even in the moments of evaluation. This shows that communication and reflection strategies whether journals, self-talk [51] or think-aloud [52], and narrative interviews [53] are all working. Ekkekakis and Brand [54] insist that knowing how people feel when they are learning, and practicing is important to predict their perseverance.…”
Section: Discussionmentioning
confidence: 92%